Efektivitas Pelaksanaan Program SMK Pusat Keunggulan (SMK PK) Melalui Dunia Industri dan Dunia Kerja (IDUKA) di SMKN PP Cianjur - Maman Suherman; Ali Ma’mur Suryana; Sani Nurani (LP. Ma'arif Janggan Magetan, 2024)
The implementation of school programs is based on planning that is prepared by considering internal and external factors. This activity is understood as a field area in realizing the school's vision and mission. The implementation of school programs requires the active involvement of all parties, one of which is the principal as the top leader in the educational unit. However, it is recognized that the implementation of programs that have been prepared does not always run according to expectations. This is due to the limited interests and financial support owned by the school. This study aims to exploit the implementation of the Center of Excellence Vocational School program through the Industrial World and the World of Work so that graduates have competence and are accepted as workers both in offices and companies. The researcher used a qualitative research method with a case study approach. Case study is a scientific activity carried out systematically and procedurally in investigating a case or multiple cases based on the context of time and place where the event occurred. (Suharyanto H. Soro (2023:37) Meanwhile, the data collection method uses observation, interview, and documentation study methods. Sample selection is done by purposive sampling. In other words, the samples in this study are school principals, teachers, and the business world of work. Research activities were carried out in the 2024 academic year. The results of the study show: (1) SMKN PP Cianjur has implemented the Center of Excellence SMK program in accordance with the established regulations; (2) SMKN PP Cianjuar has collaborated with IDUKA; (3) the Center of Excellence SMK program has a positive impact on schools, namely the creation of competent graduates in accordance with the needs of the world of work and the business world, so that graduates can be accepted by companies.